Informality in the Process of Development and Growth - Loayza, Norman V. (World Bank, Washington, DC, 2016)
"Informality" is a term used to describe the collection of firms, workers, and activities that operate outside the legal and regulatory systems. It is widespread in the majority of developing countries--in a typical developing economy, the informal sector produces about 35 percent of gross domestic product and employs 70 percent of the labor force. This paper studies informality in the context of economic development by presenting a model and projections that link informality, regulations, migration, and economic growth. This analytical framework highlights the trade-offs between formality and informality, the relationship between the different types of informality, and the connection between them and the forces of labor, capital, and productivity growth. The paper models the behavior of the informal sector based on the following fundamental asymmetry: formal firms confront higher labor costs while informal firms face higher capital costs and lower productivity. Using mandated minimum wages as the policy-induced distortion, the model first studies the static allocation of formal and informal capital and labor in a modern economy. Second, it opens the possibility of labor migration from a rudimentary economy with an ample supply of labor (rural areas or less advanced neighboring countries). Third, the model analyzes the dynamic behavior of the formal and informal sectors, considering how they affect and are affected by economic growth and labor migration. Then, the paper presents projections for the size of labor informality, in the modern and rudimentary economies, in the next two decades for a large group of countries representing all regions of the world. The projections are based on the calibration and simulation of the model and serve to discuss its usefulness and limitations.